Sociocultural vitality versus regulation policy and tourism development in preservation of traditional rural landscape: a case from Guizhou, China. Issue 2 (17th February 2021) - Jia, Ziyu; Gao, Mengyao; Xu, Shijia; Lyu, Yanping; Feng, Jicheng; Zhou, Zhengxu; Yu, Taofang; Wu, Weijia
ABSTRACT: The preservation of traditional rural landscape and community is affected not only by exogenous driving factors such as top-down policy and tourism industry, but by endogenous driving factors derived from the rural social and cultural context. The mechanism and performance of various forces has rarely been studied before. This study aims to examine the effectiveness of exogenous versus endogenous driving forces influencing rural landscape preservation from community level to individual level through a case of Tunpu villages in southwest China. Field mapping and analysis are conducted, expert scoring and questionnaire survey data are adopted, and OLS regressions are combined with qualitative analysis in this study. The results show that: 1) at community level, the socio-cultural vitality is strongly and positively correlated with the traditional rural landscape integrity; 2) at individual level, endogenous driving factors (i.e. human–environment connection and community-based organization) have more general and positive effects on residents' cognition, willingness, and behavior toward traditional rural landscape preservation comparing with the exogenous driving factors (i.e. top-down regulation policy and tourism development); resident's cognition, willingness, and behavior are homogenous despite different genders, occupations, and education levels. Our findings highlight the importance of community-based endogenous forces in promoting the preservation of traditional rural landscape. We also discuss the necessity of internal rural capacity building as well as the opportunities for a more inclusive neo-endogenous development strategy for future rural landscape preservation, policy-making, and tourism development. Overall, we hope to help promoting sustainable rural landscape preservation and utilization.